The effect of alimony on married women’s laborsupply and fertility: Evidence from state-levelreforms - Fernández Kranz, Daniel; Roff, Jennifer (Wiley, 2024)
Reforms that reduce spousal support after divorce are generally thought to reduce the bargaining power of alimony recipients as well as their incentives to participate in the traditional model of household specialization. Using the U.S. Time Use Survey and exploiting a series of recent reforms in several U.S. states that reduced the rights of eligible spouses, we find that wives surprised by the reforms reacted by increasing their labor supply, but the adjustment mechanism varied by educational group. While college educated wives' labor supply increased at the expense of time spent on housework and childcare, wives with less than a college degree sacrificed personal care and leisure time. Effects for men are generally smaller and not statistically significant. We also find a reduction in the rate of new births following the reforms, with the effect being much more pronounced in the case of women with a university education, suggesting that part of the difference in time use may be attributable to differences in preferences and the cost of children by educational levels. Since children are a marital public good, our results imply a decrease in marriage-specific investment. The estimated effects are robust to various sensitivity tests and are greater in couples with a high-income differential and therefore more exposed to changes in alimony laws.
Keywords: 53 Ciencias Económicas; ODS 3 - Salud y bienestar; ODS 5 - Igualdad de género; ODS 8 - Trabajo decente y crecimiento económico; ODS 10 - Reducción de las desigualdades